INTEGRASI NILAI NILAI ISLAM DALAM KEBIJAKAN EKONOMI: STUDI KRITIS ATAS PEMIKIRAN NIZAM AL MULK DALAM SIYASATNAMA - Fatiya Irfana Fadhila; Revalina Ellisya Putri; Rafa Rinayah; Lina Marlina (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2025)
This study aims to analyze the Islamic economic thought of Nizam al-Mulk as contained in his monumental work Siyasatnama, focusing on the principle of maslahah (public good) in government administration and its relevance to modern public governance. Nizam al-Mulk, a vizier of the Saljuk Dynasty in the 11th century, was not only known as a great statesman, but also a progressive Islamic economic thinker. Through a literature study approach and descriptive-analytical method, this study explores the theoretical and practical contributions of his thought in the aspects of taxation, bureaucratic supervision, distribution of justice, and protection of vulnerable groups in society. The results show that Nizam al-Mulk emphasized social justice through a proportional and transparent taxation system, market supervision through the institution of hisbah, and strengthening the role of the state in ensuring the basic needs of the people. He also highlighted the importance of job rotation, the provision of living wages to bureaucrats, and multiple oversight mechanisms, including the involvement of the public in the control of state officials. His approach shows alignment with contemporary challenges, such as corrupt practices, economic inequality, and weak bureaucratic accountability. Although it does not yet accommodate aspects of economic digitalization and global fiscal complexity, the basic principles put forward remain adaptive and contextual. Therefore, Siyasatnama can be utilized in the future.